El impacto de las marcas verdes en el Ecuador - Aguinda Cerda, Anderson Franklin (2023)
ABSTRACT: Green brands are defined as those that represent products or services with a lower environmental impact compared to other similar products on the market. These brands have emerged as a response to the need to move away from conventional production models and to pay special attention to environmental protection. Ecuadorian society seeks to satisfy its needs through the acquisition of products and services, largely provided by both national and international brands, including transnational companies operating in Ecuadorian territory. These commercial brands occupy a significant place in the local market.The purpose of this research is to carry out a legal and doctrinal study aimed at establishing the legal and commercial particularities of green trademarks and their real impact on the conservation of the environment in Ecuador. To this end, a mixed approach has been used, combining legal, commercial and environmental aspects, to obtain a more complete and profound vision of the subject of study. The technique used is the survey, applying a quantitative data collection instrument (questionnaire with Likert-type scaling) to consumers and producers with the purpose of carrying out the validation by means of triangulation by method. Finally, the results show that green brands contribute to environmental conservation in Ecuador, Keywords: Green Marks, Conservation, Environmental Impact, Sustainable Development, Environmental Protection.